Influences of ongoing and projected environmental change in range margin Sequoia sempervirens (coast redwood) forests - Woodward, Brian David, author; Evangelista, Paul, advisor; Ex, Seth, committee member; Jarnevich, Catherine, committee member; Romme, William, committee member (Colorado State University. Libraries, 2021)
To view the abstract, please see the full text of the document.